y-8=(18)(x-6)

The standard form of a linear equation is Ax+By=C.

Multiply both sides by 8.

8(y-8)=8(18(x-6))

Apply the distributive property.

8y+8⋅-8=8(18(x-6))

Multiply 8 by -8.

8y-64=8(18(x-6))

8y-64=8(18(x-6))

Apply the distributive property.

8y-64=8(18x+18⋅-6)

Combine 18 and x.

8y-64=8(x8+18⋅-6)

Cancel the common factor of 2.

Factor 2 out of 8.

8y-64=8(x8+12(4)⋅-6)

Factor 2 out of -6.

8y-64=8(x8+12⋅4⋅(2⋅-3))

Cancel the common factor.

8y-64=8(x8+12⋅4⋅(2⋅-3))

Rewrite the expression.

8y-64=8(x8+14⋅-3)

8y-64=8(x8+14⋅-3)

Combine 14 and -3.

8y-64=8(x8+-34)

Move the negative in front of the fraction.

8y-64=8(x8-34)

Apply the distributive property.

8y-64=8×8+8(-34)

Cancel the common factor of 8.

Cancel the common factor.

8y-64=8×8+8(-34)

Rewrite the expression.

8y-64=x+8(-34)

8y-64=x+8(-34)

Cancel the common factor of 4.

Move the leading negative in -34 into the numerator.

8y-64=x+8(-34)

Factor 4 out of 8.

8y-64=x+4(2)-34

Cancel the common factor.

8y-64=x+4⋅2-34

Rewrite the expression.

8y-64=x+2⋅-3

8y-64=x+2⋅-3

Multiply 2 by -3.

8y-64=x-6

8y-64=x-6

Rewrite the equation with the sides flipped.

x-6=8y-64

Subtract 8y from both sides of the equation.

x-6-8y=-64

Move -6.

x-8y-6=-64

x-8y-6=-64

Add 6 to both sides of the equation.

x-8y=-64+6

Add -64 and 6.

x-8y=-58

x-8y=-58

Rewrite in Standard Form y-8=(1/8)(x-6)